Third Ghana Economic Update : Agriculture as an Engine of Growth and Jobs Creation - World Bank Group (World Bank, Washington, DC, 2018)
In September 2017, Ghana's economy expanded for the fifth successive quarter by 9.3 percent compared to just 4.3 percent in September 2016. This reflects continued high levels of growth in the industry sector, driven by mining and petroleum. Oil production rose by 16.6 percent compared with a contraction of 11.2 percent for the similar period of 2016, as production increased in all existing oil fields and some new production came online. For instance, the Jubilee Fields increased production with the resolution of technical difficulties that arose in March 2016; and new production came online in the Offshore Cape Three Points (OCTP) Fields.